Pengukuran Fleksibilitas Dalam Industri Manufaktur Dengan Menggunakan Objective Matrix (OMAX) dan Entropy - Wakhid Ahmad Jauhari (Performa: Media Ilmiah Teknik Industri, 2006)
As globalization of markets raises competitive pressures, one essential requirement for the survival of organizations is their capability to meet competition. Market needs cause unceasing changes in the life cycle, shape, quality and price of products. Manufacturing flexibility is an effective way to face up to the uncertainties of this rapidly changing environment and it is defined as the ability to absorb various disturbances which occur in production systems, as well as the ability to incorporate and exploit new technological advances and work practices. The aim ofthis paper is to measure capability and requirement offlexibility in manufacturing system. We propose Objective Matrix (OMAX) and Entropy integration method to measure flexibility.